Effect of different pre and post emergent application of herbicides on the yield, quality and economics in Indian mustard (Brassica juncea L.) under Tarai region of Uttarakhand - Swati Dash,; Anil Shukla,; Supriya,; Shashank Patel,; Monica Yaying,; Sudarshan S., (Annals of Agricultural Research, 2024)
A field experiment was conducted during Rabi season of 2019-2020 at Oilseed Agronomy (E5) Block of Norman E. Borlaug Crop Research Centre of Govind Ballabh Pant University of Agriculture & Technology, Pantnagar (Uttarakhand) for exploration of weed management module for Indian mustard (Brassica juncea L.) under humid tarai conditions of Uttarakhand. The experiment was laid out in Randomized Block Design taking three replications of thirteen treatments. The treatments undertaken were Pendimethalin @ 1kg a.i./ ha (P E), Pendimethalin @0.5kg a.i./ha (P E), Pendimethalin @1kg a.i./ha (P E) + HW 30 DAS, Pendimethalin @0.5kg a.i./ha (P E)+ HW 30 DAS, Oxadiargyl @0.09kg a.i./ha (P E), Oxadiargyl @0.045kg a.i./ha (P E), Oxadiargyl @0.09kg a.i./ha (P E) + HW 30 DAS, Oxadiargyl @0.045kg a.i./ha (P E) + HW 30 DAS, Clodinafop @0.06kg a.i./ha (Po E), Clodinafop @0.03kg a.i./ha (Po E), Clodinafop @0.06kg a.i./ha (Po E)+ HW 60 DAS, Clodinafop @0.03 kg a.i./ha (Po E) + HW 60 DAS and Control (Weedy Check). Indian mustard variety NRCHB- 101 was sown in a geometry of 30cm × 10cm on 01 November 2019 and harvested on 21 March 2020. Higher seed yield (3373 kg/ha), oil (1364 kg/ha) and protein yield (898 kg/ha), net return (114120`ha-1) and B: C ratio (3.2) was obtained with application of Pendimethalin @1kg a.i./ha (P E) + HW 30 DAS.